2017
DOI: 10.1007/s11030-017-9799-7
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based pharmacophore design and virtual screening for novel potential inhibitors of epidermal growth factor receptor as an approach to breast cancer chemotherapy

Abstract: Cancer cells are described with features of uncontrolled growth, invasion and metastasis. The epidermal growth factor receptor subfamily of tyrosine kinases (EGFR-TK) plays a crucial regulatory role in the control of cellular proliferation and progression of various cancers. Therefore, its inhibition might lead to the discovery of a new generation of anticancer drugs. In the present study, structure-based pharmacophore modeling, molecular docking and molecular dynamics simulations were applied to identify pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…With this regard, a literature survey revealed that molecular docking into the ATP binding site of EGFR (protein data bank ID: 1M17) was a robust strategy for identification of effective EGFR inhibitors endowed with cytotoxic properties [58][59][60]. In the current study, docking simulations using the crystal structure of EGFR, co-crystallized with its inhibitor erlotinib, has been performed to elucidate the interactions of the active cytotoxic agents 5a, 5e, 5g, and 5h at the 'Erlotinib' binding domain of tyrosine kinase enzyme (protein data bank ID: 1M17), by using Autodock 4.2 ( Table 2).…”
Section: Identification Of Potential Anticancer Drugmentioning
confidence: 99%
“…With this regard, a literature survey revealed that molecular docking into the ATP binding site of EGFR (protein data bank ID: 1M17) was a robust strategy for identification of effective EGFR inhibitors endowed with cytotoxic properties [58][59][60]. In the current study, docking simulations using the crystal structure of EGFR, co-crystallized with its inhibitor erlotinib, has been performed to elucidate the interactions of the active cytotoxic agents 5a, 5e, 5g, and 5h at the 'Erlotinib' binding domain of tyrosine kinase enzyme (protein data bank ID: 1M17), by using Autodock 4.2 ( Table 2).…”
Section: Identification Of Potential Anticancer Drugmentioning
confidence: 99%
“…Then, cells were washed with PBS before adding MTT solution (20 µL of 5 mg/mL MTT solution per each well). After 4 h, the absorbance of the developed color of each well was measured at 570 nm using a microplate reader (ELx800 Absorbance Microplate Reader, BioTek, Winooski, USA) (Mosayebnia et al, 2014), (Tabasi et al, 2013), (Mahernia et al, 2017).…”
Section: In Vitro Cytotoxicity Testmentioning
confidence: 99%